Thermoheliodome Testing: Evaluation Methods for Testing Directed Radiant Heat Reflection. (November 2015) - Calabrò, Emanuele; Meggers, Forrest; Teitelbaum, Eric; Guo, Hongshan; Gmachl, Claire; Penello, Germano Maioli
Abstract: The Thermoheliodome is a prototype experimental pavilion that produces comfort through the manipulation of the mean radiant temperature generated by a combination of evaporative cooling and radiant heat reflection. We present the development of a sensing and analysis method for measuring the impact on radiant temperature and other performance data for the space, along with the initial system measurements. This is an environmental control station through which low cost microcontrollers enable distributed networked nodes to take measurements of relevant system parameters. The system measurements show a reduction of mean radiant temperature by 2-3 °C using evaporative cooling and strategic reflection.